Country Land Erfpacht Rights Formerly: Placed By People - Karyoto, Karyoto (Prosiding Seminar; 2020: 2020 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.33, 2020)
This study aims to determine the Land for Erfpacht Rights Formerly owned by Dutch Foreign Residents occupied by the people is State land or called former Western rights land, which was once denounced by Dutch Foreign Residents, since the issuance of UUPA No. 5 of 1960 dated 24 September 1960 to the present year, this kind of land often creates disputes between former rights holders and people who occupy land. The fundamental problem is that many issued overlapping National Land Laws, while UUPA No. 5 of 1960 has not been firm in explaining, describing the meaning and substance of State land obtained from former Western rights, resulting in occupation of land by the people without obtaining permission or approval from former rights holders, because the land is abandoned or not properly maintained.